A song of comfortable chairs [large type] - McCall Smith, Alexander, 1948- (McCall Smith, Alexander, 1948- No. 1 Ladies Detective Agency series, 2022)
"Grace Makutsi's husband, Phuti, is in a bind. An international firm is attempting to undercut his prices in the office furniture market. Meanwhile, Mma Makutsi is approached by an old friend who has a troubled son. Grace and Phuti agree to lend a hand, but the situation is more than they can handle on their own. It will require not only all of their patience and dedication, but also the help of Mma Ramotswe and the formidable Mma Potokwani. Mma Makutsi deals with it all with her usual grace. That, along with the kindness, generosity, and good sense that the No. 1 Ladies' Detective Agency is known for, assure us that in the end, all these matters will be set right"--